2020
DOI: 10.1155/2020/9595036
|View full text |Cite
|
Sign up to set email alerts
|

Salidroside-Mediated Autophagic Targeting of Active Src and Caveolin-1 Suppresses Low-Density Lipoprotein Transcytosis across Endothelial Cells

Abstract: Subendothelial retention of apolipoprotein B100-containing lipoprotein, such as low-density lipoprotein (LDL), is the initial step of atherogenesis. Activation of autophagy exhibits beneficial effects for the treatment of atherosclerosis. In our previous study, we demonstrated that hyperglycemia suppressed autophagic degradation of caveolin-1, which in turn resulted in acceleration of caveolae-mediated LDL transcytosis across endothelial cells and lipid retention. Therefore, targeting the crossed pathway in au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 48 publications
(79 reference statements)
0
11
0
Order By: Relevance
“…Therefore, potential drugs for OSA-related atherosclerotic cardiovascular diseases remain to be further investigated. Salidroside can improve atherosclerosis in high fat diet-fed ApoE -/- mice ( Bai et al, 2020 ; Song et al, 2021 ). However, the effect of salidroside on CIH-related atherosclerosis has not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, potential drugs for OSA-related atherosclerotic cardiovascular diseases remain to be further investigated. Salidroside can improve atherosclerosis in high fat diet-fed ApoE -/- mice ( Bai et al, 2020 ; Song et al, 2021 ). However, the effect of salidroside on CIH-related atherosclerosis has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Salidroside exhibited activity similar to that of Rhodiola extract. Salidroside improved CIH-mediated myocardial cell apoptosis ( Zhong et al, 2010 ; Lai et al, 2014 ), chronic persistent hypoxia-induced pulmonary hypertension ( Chen et al, 2016 ) and high fat diet-related atherosclerosis ( Xing et al, 2015 ; Bai et al, 2020 ; Song et al, 2021 ) in animal models. Moreover, salidroside suppresses oxidative stress-induced HUVECs cell injury ( Zhao et al, 2013 ; Zhu et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…2C, E). LDL uptake by ECs is not only an intermediate step of LDL transcytosis, but is also crucial to atherogenesis [36]. Therefore, the concentration of LDL in the ECs is an indicator of LDL transcytosis.…”
Section: Sirt6 Reversed High Glucose-induced Ldl Transcytosismentioning
confidence: 99%
“…4,5 Studies have shown that SAL has antiatherosclerotic effects, 6,7 and the mechanisms involved include various pathways such as oxidative stress, inflammation, mitochondrial dysfunction, autophagy, and AMP-activated protein kinase signal transduction. 8–11…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Studies have shown that SAL has antiatherosclerotic effects, 6,7 and the mechanisms involved include various pathways such as oxidative stress, inflammation, mitochondrial dysfunction, autophagy, and AMP-activated protein kinase signal transduction. [8][9][10][11] In fact, as a chronic inflammatory disease, a large part of the treatment of atherosclerosis benefits from its inhibition of inflammatory signaling. Liu et al showed that SAL reduced atherosclerotic plaque formation by inhibiting NOD-like receptor protein 3 (NLRP3)-associated endothelial cell pyroptosis.…”
Section: Introductionmentioning
confidence: 99%